Merdeka Belajar: Memahami Konsep Pembelajaran Masa Kini - Kamila, Qurota A'yun Ning; ASBARI, MASDUKI; DARMAYANTI, EULIS; Nuraida (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to understand how the Merdeka curriculum shapes contemporary learners. This study's report utilizes a qualitative descriptive method, employing a listening-and-note-taking approach to gather data from the oral narration on the YouTube channel "Belajar Era Digital" titled "Understanding the Concept of Learning in the Merdeka Curriculum," presented by Iswahyudi Rahman S.Pd., CERT.ELS., MIE. The study's findings explain that the Merdeka curriculum concept focuses on developing students' skills and character, not just academic knowledge. Learning is designed to prepare students to face future challenges. This concept prioritizes student-centered learning based on students' needs, not just their desires. The development of emotions, cognitive skills, and character is emphasized with the goal of creating an innovative and socially beneficial generation.